2010
DOI: 10.1007/s10165-010-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

Two subtypes of Churg–Strauss syndrome with neuropathy: the roles of eosinophils and ANCA

Abstract: The aim of this study was to clarify the differences in the pathogenesis of neuropathy between myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA)-positive and -negative patients with Churg-Strauss syndrome (CSS). Eight MPO-ANCA-positive and 14 MPO-ANCA-negative patients were included. In addition to the standard histology, nerve biopsies were examined, employing immunohistochemistry for eosinophil major basic protein and electron microscopy. The groups did not differ significantly in clinical profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…3 In the article by Sabl e-Fourtassou et al, 3 ''ELISA assay showed that serum specimens of 34 of 39 patients with perinuclear ANCA (5 patients' specimens were not tested) had anti-MPO specificity.'' 2 More recently, similar results were obtained by Baldini et al 6 and Oka et al, 7 who found anti-MPO antibodies in 15 (39%) of 38 and 8 (36.4%) of 22 patients, respectively.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…3 In the article by Sabl e-Fourtassou et al, 3 ''ELISA assay showed that serum specimens of 34 of 39 patients with perinuclear ANCA (5 patients' specimens were not tested) had anti-MPO specificity.'' 2 More recently, similar results were obtained by Baldini et al 6 and Oka et al, 7 who found anti-MPO antibodies in 15 (39%) of 38 and 8 (36.4%) of 22 patients, respectively.…”
supporting
confidence: 80%
“…7 In conclusion, Healy et al 1 confirm that ANCAs (mainly with specificity for MPO) are present in approximately 40% of patients with CSS and that ANCA status correlates with organ involvement, even though some associations should be verified in more numerous case series. …”
mentioning
confidence: 74%
“…Neuropathy is frequently described in the literature as occurring in around 70% of cases 12 26. Owing to the eosinophilic infiltration and the release of toxic mediators, this leads to small vessel arteritis of peripheral nerves.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of high titer of ANCA hallmarks the vasculitic disease complications, as some large studies demonstrated that ANCA were positive in among 30-40% of EGPA patients and that ANCA-positive patients more frequently had peripheral neuropathy, glomerulonephritis, purpura and CNS involvement (which are due to small-vessel vasculitis) [1,9,10]. Thus ANCA should be tested in patients with cerebrovascular disease associated with systemic inflammation or eosinophilia and anamnestic asthma.…”
Section: Discussionmentioning
confidence: 99%